Phototherapy in the Treatment of Diabetic Foot — A Preliminary Study - Mikołajczyk Zbigniew; Nowak Iwona; Kawiński Andrzej; Mik Michał (AUTEX Research Journal, 2021)
The first part of the publication presents a substantively insightful literature study on the essence and effects of light waves on wound healing in living organisms, including the use of phototherapy in the treatment of the diabetic foot. A knitted textile dressing was designed and manufactured for phototherapy of patients with diabetes suffering from diabetic foot syndrome (DFS). The proposed solution is intended for the treatment of dermal tissues within the patient's foot affected because of diabetic disease at an early stage. Thus, the use of a knitted dressing with incorporated fiber optic structures and powered by a semiconductor laser emitting a 405 nm light wave from its entire surface would prevent further anomalies of the patient's tissues and help to avoid surgical intervention.